Origami with small molecules: exploiting the C–F bond as a conformational tool - Patrick Ryan; Ramsha Iftikhar; Luke Hunter (Beilstein Journal of Organic Chemistry)
When present within an organic molecule, the C–F bond tends to align in predictable ways with neighbouring functional groups, due to stereoelectronic effects such as hyperconjugation and electrostatic attraction/repulsion. These fluorine-derived conformational effects have been exploited to control the shapes, and thereby enhance the properties, of a wide variety of functional molecules including pharmaceutical agents, liquid crystals, fragrance chemicals, organocatalysts, and peptides. This comprehensive review summarises developments in this field during the period 2010–2024.